Distinct responses of Copepoda and Cladocera diversity to climatic, environmental, and geographic filters in the La Plata River basin - Perbiche-Neves, Gilmar; Saito, Victor Satoru; Simoes, Nadson Ressye; Debastiani-Junior, Jose Roberto [UNESP]; Oliveira Naliato, Danilo Augusto de [UNESP]; Nogueira, Marcos Gomes [UNESP] (Springer, 2019)
The distribution of freshwater cladocerans and copepods and the drivers of beta diversity along La Plata basin were studied. We propose that local environmental conditions, dispersal limitation, and climate affect cladocerans and copepods differently owing to their variances in terms of life strategies. We calculated beta diversity using four dissimilarity metrics, and also the relative importance of spatial, environmental, and climatic variables by partitioning variance and forward selection procedure coupled with a partial redundancy analysis. Beta diversity patterns were characterized by a high turnover in the subbasins and a small contribution of nestedness. Forward selection evidenced the influence of total nitrogen and total suspended matter for both copepods and cladocerans, suggesting a strong role of eutrophication in controlling their turnover, but spatial distance, precipitation, and mean temperature of winter were related only to copepods. The last one suggests a likely role of geographic isolation driving speciation and endemism in Copepoda and reinforces the strong effect of climatic variation resulting in the high endemism patterns one finds in the Neotropical region.
Keywords: Zooplankton; Metacommunities; Biodiversity; Lakes; Running waters